RELIGIOUS EDUCATION CHILDREN IN THE FAMILY CROSS RELIGIOUS PERSPECTIVE - Hamdanah, Hamdanah (LP2M IAIN Palangka Raya, 2012)
Family is one of natural education center. Parents are naturally encouraged to educate and guide their children to be mature who have a decent life, to be happy in this world and hereafter. Because the religious education that was given by parents to children has a major influence in forming the character of the growth and development of the children.Children who get more religious exercise in their childhood will get a stronger religious basic in them selves when they are being adult, so they can apply it in their life. Religious diversity is aÂ Sunnatullahthat must be accepted by humans objectively, even the Lord reminded that everybody has been given a law and way in belief, then how humans compete to do goodness on the earth.The multi religions perspective, religious education in family basically shows similarities in pattern, goal and material. Its pattern and goal is to establish a good personality, to the Almighty God and also the other creatures, in order to make a responsible person. Different religions in a family is quite difficult to provide religious education to the children, though it seems harmonious, but it gets problems and psychological effects in the process of planting a belief or ideology to the children.